Retração rápida de caninos associada ao levantamento do seio maxilar - Ribeiro, Paulo Renato Carvalho (2007)
INTRODUCTION: Rapid canine distalization using distraction of the periodontal ligament is a tooth movement technique that allows to close the space of extraction of first premolars in about 2 or 3 weeks, reducing orthodontic treatment time considerably. The surgical technique for this procedure is reasonably simple, however, during surgery in the maxilla, always exists the risk of sinus injury when the sinus membrane is close to the apex of canines and first premolars. AIM: The aim of this study is to present a case report showing a modification of the original technique proposed by Liou and Huang, where the maxillary sinus membrane lifting procedure was undertaken in a simple way, leaving it intact, and permitting a safer and more controlled protocol to start the rapid canine retraction. CONCLUSION: Rapid canine retraction is a viable procedure and maxillary sinus lifting may be helpful in providing the tooth movement.